AKRAB PENTINGNYA MEMBANGUN BRAND BAGI USAHA RADIO SIARAN KOMERSIAL LOKAL DI DIY - Wahyu Sudarmawan (AKADEMI KOMUNIKASI RADYA BINATAMA, 2017)
ABSTRACTBusiness competition to manage radio broadcasting in DIY so tight, the number of terrestrial radio is too much and not balanced with the number of radio listeners that resulted in the community is often confused in choosing & know the name of the radio station. This also affects advertisers who are also confused about selecting suitable broadcast radio as a means of promoting their business. The public can only recognize the radio from the program & certain uniqueness-uniqueness that characterizes a radio station so it takes the ingenuity of radio management in building & creating the brand.